PENDIDIKAN ISLAM PERSPEKTIF IKHWANUS SHAFA DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM KONTEMPORER - Huswatul Hasanah (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2023)
Education is one of the paths that humans must take to become happy. A person can improve their quality in the form of physical and mental abilities through the educational process. Ikhwanus Shafa, is a group of Islamic thinkers who study and offer concepts of Islamic education; which includes religious-rational understanding. This article aims to find out about the educational perspective of the Ikhwanus Shafa and its relevance to contemporary Islamic education. The research method in this writing is library research which is qualitative in nature. The primary data source for this writing is a book by Maragustam entitled "Philosophy of Islamic Education Towards Character Formation in Facing Global Currents". The secondary data sources for writing use books and journals that are relevant to the discussion. Data collection techniques use documentation. The data analysis technique uses content analysis. The results and discussion in this paper are that according to Ikwanus Shafa the aim of education must be linked to religion; the curriculum must include logic, philosophy, psychology, study of divine religious books, prophecy, sharia sciences, and exact sciences; Teaching methods must teach from concrete to abstract, namely by presenting examples during learning. The relevance of Ikhwanus Shafa's educational thoughts to contemporary Islamic education is relevant based on the regulations/policies in Law no. 20 of 2003. However, problems and challenges were found that were not in line with the rules/policies in their implementation. The implication of this research is that we can know that Islamic education will continue to exist and be relevant to the progress of the times when the implementers of educational activities themselves are still willing to open themselves to progress and compromise with the latest technology.